MENINGKATKAN KEAHLIAN DASAR SISWA SMK DALAM PERANCANGAN SISTEM INFORMASI - Saragih, Saut Pintubipar; Svinarky, Irene (ASOSIASI IDEBAHASA KEPRI, 2025)
In the rapidly evolving landscape of information technology, equipping students with practical and industry-relevant skills is essential before they transition into the workforce. This community service program was designed to conduct training initiative to strengthen students’ competencies in information system design. The objective of the program was to enhance participants’ ability to analyze user requirements, model system architectures, and implement structured system design methodologies. Throughout the training, students were introduced to core concepts of system designing such as Data Flow Diagrams, user interface wireframing, and tools related to it. In addition, students gained hands-on experience in using professional tools like draw.io and Figma, which are commonly utilized in system analysis and design processes in real-world IT projects. This training emphasizes the application of structured analysis techniques, logical data modeling, and fundamental software development lifecycle (SDLC) principles. By the end of the program, students demonstrated improved abilities to translate business requirements into technical specifications and were better prepared to engage in entry-level roles or further studies related to software engineering, business informatics, or systems analysis. The initiative highlights the importance of early exposure to system thinking and technical documentation in secondary vocational education, particularly for those pursuing a future in information systems development. The program not only expanded students’ technical knowledge but also encouraged analytical thinking and collaborative problem-solving, which are critical in the field of computer science and information systems